2019
DOI: 10.1088/2043-6254/ab38af
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis temperature and time affect size, distribution and bioactivity of Tetradenia riparia-produced AgNPs

Abstract: Leaf extracts of Tetradenia riparia were used to synthesise silver nanoparticles (AgNPs) using 1 mM silver nitrate for 6, 12 and 24 h at room temperature (RT) and at 80 °C. There were no significant differences in nanoparticle (NP) yield between synthesis at RT and at 80 °C, and amongst the different synthesis times (6, 12 and 24 h) (p>0.05). Fourier transformed infrared spectroscopy analyses confirmed the presence of functional groups. The AgNPs were mostly spherical in shape. The largest AgNPs were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The spatial distribution of Tetradenia riperia has been documented in various areas of African countries such as Rwanda 53 , Madagascar 54 , South Africa 55 , Uganda 56 and Tanzania 57 in which its medicinal potential has been attributed to abundant phytocompounds with antimicrobial effects 51 . Literature has reported the use of Tetradenia riperia leaves in the synthesis of various nanoparticles such as silver 58 , 59 . To the best of our knowledge, no study has reported on the synthesis of Ag–ZnO nanocomposites by using the aqueous leaves extract of Tetradenia riperia .…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution of Tetradenia riperia has been documented in various areas of African countries such as Rwanda 53 , Madagascar 54 , South Africa 55 , Uganda 56 and Tanzania 57 in which its medicinal potential has been attributed to abundant phytocompounds with antimicrobial effects 51 . Literature has reported the use of Tetradenia riperia leaves in the synthesis of various nanoparticles such as silver 58 , 59 . To the best of our knowledge, no study has reported on the synthesis of Ag–ZnO nanocomposites by using the aqueous leaves extract of Tetradenia riperia .…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution of Tetradenia riperia has been documented in various areas of African countries such as Rwanda [45], Madagascar [46], South Africa [47], Uganda [48] and Tanzania [49] in which its medicinal potential has been attributed to abundant phytocompounds with antimicrobial effects [43]. Literature has reported the use of Tetradenia riperia leaves in the synthesis of various nanoparticles such as silver [50,51]. To the best of our knowledge, no study has reported on the synthesis of Ag-ZnO nanocomposites by using the aqueous leaf extract of Tetradenia riperia.…”
Section: Introductionmentioning
confidence: 99%